MiR-191-5p is upregulated in culture media of implanted human embryo on day fifth of development - Ricardo Josué Acuña-González; Mercedes Olvera-Valencia; Jorge Skiold López-Canales; Jair Lozano-Cuenca; Mauricio Osorio-Caballero; Héctor Flores-Herrera (BMC, 2021)
Abstract Background Morphological features are the most common criteria used to select human embryos for transfer to a receptive uterine cavity. However, such characteristics are not valid for embryos in cellular arrest. Even aneuploid embryos can have normal morphology, and some euploid embryos have aberrant morphology. The aim of this study was to quantify the expression profile of hsa-miR-21-3p, -24-1-5p, -191-5p, and -372-5p in culture media on day 5 of in vitro embryo development, and compare the profiles of two groups of media classified by outcome: successful (n = 25) or unsuccessful (n = 25) implantation pregnancy. Methods Fifty patients were accepted in the Department of Reproductive Biology of a Hospital in México City, based on the Institutional inclusion criteria for in vitro fertilization. Embryos were transferred to the women on day 5 of cultivation, and the culture media were collected. RNA was isolated from each culture medium with TRIzol reagent, and microRNA (miRNA) expression was detected through RT-PCR with specific primers. Expression bands were quantified by reading optical density. Results There was a 5.2-fold greater expression of hsa-miR-191-5p in the pregnancy-related culture media (p ≤ 0.001) and a 1.6-fold greater level of hsa-miR-24-1-5p (p = 0.043) in the media corresponding to non-pregnant women. No significant difference existed between the two groups hsa-miR-21-3p (p = 0.38) or hsa-miR-372-5p (p = 0.41). Conclusions Regarding adequate in vitro embryo development, hsa-miR-191-5p could possibly represent a positive biomarker, while has-miR-24-1-5p may indicate poor prognosis. This former miRNA modulates IGF2BP-1 and IGF2R, associated with the implantation window. On the other hand, hsa-miR-24-1-5p may be related to a poor prognosis of human embryo development.